Cross-protectivity of henipavirus soluble glycoprotein in an in vivo model of Nipah virus disease - Findlay-Wilson, Stephen; Thakur, Nazia; Crossley, Lucy; Easterbrook, Linda; Salguero, Francisco J.; Ruedas-Torres, Ines; Fotheringham, Susan; Kennedy, Emma; Bailey, Dalan; Dowall, Stuart (Frontiers in Immunology, 2025)
IntroductionNipah virus (NiV) is one of a group of highly pathogenic viruses classified within the Henipavirus genus. Since 2012 at least 11 new henipa-like viruses have been identified, including from new locations and reservoir hosts; the pathogenicity of these new viruses has yet to be determined, but two of them have been associated with morbidity, including fatalities.MethodsThe efficacy and cross-reactivity of two vaccine candidates derived from the soluble glycoproteins of both NiV and Hendra virus (HeV) was evaluated in our recently established hamster model.ResultsBoth vaccine preparations resulted in strong humoral responses against NiV antigenic targets, demonstrating cross-reactive immunity. Efficacy was determined through challenge of hamsters with NiV Malaysian (NiV-M) strain. 100% of the hamsters survived a lethal challenge dose after prime/boost immunisation with glycoproteins derived from both NiV and HeV in the presence of adjuvant, with clinical signs and pathology being significantly reduced in immunised animals.DiscussionThis is first time the NiV and HeV soluble glycoproteins have been compared in the NiV-M hamster challenge model in the presence of Alhydrogel and AddaVax, providing evidence that glycoproteins from closely related henipavirus species can provide cross-protectivity against infection from alternate henipaviruses, supporting the potential of an effective pan-henipavirus vaccine for use in a frontline outbreak response.